Energy consumption and emissions from the road transport in Spain: a conceptual approach - Pérez-Martínez, Pedro J. (Transport, 2012)
The interurban road transport is one of the largest sources of emissions within all the economical sectors of Spain and accounts for 30% of the total energy consumption and subsequent CO2emissions. Fuel consumption, mostly gasoline and diesel, has decreased by −0.7% between 2004 and 2009 despite the increase of vehicle fleet (14.7%) and related travelled performances (3.1%). The paper estimates the energy consumption and subsequent emissions of CO2 and pollutants, CO, NOx, PM and NMVOC, of the interurban road transport in Spain for the period 2004–2009 by the use of a conceptual procedure. This procedure makes an effort to allocate the fuel sales, liters of diesel and gasoline, across different categories of vehicles (ages and technologies) operating on the interurban Spanish roads. In order to elaborate the inventory of energy consumption and emissions, the procedure uses the emission factors from the Copert process-based model, optimized for the Spanish interurban driving conditions. According to the inventory, total CO2 emissions have decreased from 68.0 Mt of CO2in 2004 to 66.9 Mt (−1.6%). This trend is due to diesel road vehicles. The CO2 emissions of gasoline vehicles and the total emission of related pollutants followed a downward trend due to technological improvements of vehicles and decrease of gasoline consumption. The CO2 emissions of diesel vehicles and the total emission of related pollutants followed an upward trend due to the increase of diesel consumption despite technological improvements of vehicles. Better estimates of energy consumption and emissions are possible in the future by using specific emission factors for different vehicle categories based on telemetric systems. First Published Online: 21 Dec 2012